2013
DOI: 10.1007/s00402-013-1902-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of the augmented PFNA: a prospective multicenter trial

Abstract: MethodsIn 5 european clinics, 62 patients (79 % female, mean age 85.3 years) suffering from an osteoporotic pertrochanteric fracture (AO 31) were treated with the augmented PFNA ® . The primary objectives were assessment of activities of daily living, pain and mobility. Furthermore, the X-rays were analyzed for the cortical thickness index, changes of the trabecular structure around the cement and the hip joint space. Results The mean follow-up time was 15.3 months. We observed callus healing in all cases. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
0
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 44 publications
5
46
0
10
Order By: Relevance
“…Therefore, we used a cyclic loading protocol, because this seems to best approximate the clinical loading scenario. Preliminary clinical studies showed a decrease in implant loosening rates with cement augmentation in the osteoporotic proximal femur [20] and spine [38]. Cement augmentation of sacroiliac screw fixation has been reported in small case reports and series [41,46], and few complications were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we used a cyclic loading protocol, because this seems to best approximate the clinical loading scenario. Preliminary clinical studies showed a decrease in implant loosening rates with cement augmentation in the osteoporotic proximal femur [20] and spine [38]. Cement augmentation of sacroiliac screw fixation has been reported in small case reports and series [41,46], and few complications were reported.…”
Section: Discussionmentioning
confidence: 99%
“…In einer Multicenterstudie, in der 62 Patienten mit einer osteoporoseassoziierten pertrochantären Femurfraktur in 5 Zentren prospektiv erfasst und mit einem zementaugmentierten PFNA versorgt wurden, zeigten sich gute funktionelle Ergebnisse nach einer mittleren Nachuntersuchungszeit von 15,3 Monaten [18]. Dabei konnten keine zementassoziierten Komplikationen beobachtet werden, weshalb die Zementaugmentation des PFNA als sicheres Verfahren eingestuft wurde.…”
Section: Ergebnisse Mit Dem Zementaugmentierten Pfnaunclassified
“…In klinisch-prospektiven Untersuchungen zeigte die Zementaugmentation des PFNA bei orthogeriatrischen Patienten mit pertrochantärer Femurfraktur gute funktionelle Ergebnisse ohne Hinweise auf zementassoziierte Komplikationen [18,20].…”
Section: Pfna-marknagelosteosyntheseunclassified
See 1 more Smart Citation
“…Auch der Einsatz am Patienten zeigt erste vielversprechende Ergebnisse und keine spezifisch erhöhten Komplikationen im Langzeitverlauf [11,12].…”
unclassified